Heaven is for real : a little boy's astounding story of his trip to heaven and back - Burpo, Todd.; Vincent, Lynn. (Nashville, Tenn. : Thomas Nelson, 2010)
A father recounts his 3 year old son's encounter with Jesus and the angels during an emergency appendectomy.
Includes bibliographical references.
Keywords: Burpo, Colton, -- 1999-; Heaven -- Christianity; Near-death experiences -- Religious aspects -- Christianity